(untitled) (Studia theodisca, 2021)
This study focuses on Musil’s contributions to Heimat, a propaganda newspaper published by the k.u.k. Kriegspressequartier during the last months of World War I. As the authorship of the Heimat articles is controversial, we performed a series of stylometric analyses, which allowed us to attribute ten texts to the Austrian writer. Our approach introduces new elements and data into the debate on authorship, thus opening a productive dialogue between computational, archival and stylistic research.